Hizbullah’s Post-Islamist Trends in the Performing Arts - Joseph Alagha (Religions, 2020)
This article outlines Hizbullah’s shift to post-Islamism and its various cultural activities in Lebanese society that underpin this shift. The Party’s involvement in these activities is integrated in current research on post-Islamism and its various social, political, and cultural manifestations. In its Islamist stage, Hizbullah anathematized the Lebanese political system and state institutions. In its post-Islamist phase, Hizbullah became pragmatic by embarking on a policy of opening-up (infitah) in politics along with cultural and social practices. This article studies Hizbullah’s popular culture and lifestyles by focusing on its purposeful art or ‘resistance art’, which is a cultural resistance against oppression, domestic deprivation, disenfranchisement, and repression, as well as foreign aggression, invasion, occupation, and subjugation. Hizbullah exploits the concepts of cultural citizenship and cultural politics to encourage, in mixed gender spaces, purposeful performing arts: music, dancing, singing, revolutionary theater, and satire. Hizbullah appears to equate modernity with European art forms rather than indigenous forms. In its ideology and politics, Hizbullah fluctuated between Islamism and post-Islamism. While in its performing arts, Hizbullah conveyed a post-Islamist face legitimized by the principle of maslaha (public interest).